ADIÇÃO DO FATOR ATIVOS INTANGÍVEIS AO MODELO DE PRECIFICAÇÃO DE ATIVOS DE FAMA & FRENCH - Honorio, Filippi Mickael Martini (2022)
This research examined the effect of intangible assets on the performance of asset pricing models to explain returns in the context of the Brazilian capital market. In view of this, the concepts of the Arbitrage Pricing Theory (APT) were used, when testing the CAPM, Three, Four and Five Factor models, all with the inclusion of the intangible assets variable, measured from the VAICTM model, by Pulic (1998), which is based on the Value Added Statement (VAD), an important accounting statement that measures the generation of wealth of a company, highlighting the expenses with personnel and the added value, crucial elements for the calculation of intangible assets. The methodology for data analysis was the two-step process of Fama and MacBeth (1973), conducted by time series regression for the first step and cross section regression for the second step. The results of the first-step regressions indicated statistical significance in explaining returns only for the Rm-Rf variable (excess of market return over the risk-free rate), confirming the validity of the CAPM model for the Brazilian capital market. Even though the other models have not shown significance, there was an increase in the explanatory power of the Rm-Rf variable, with the inclusion of other factors, as occurred with research in developed countries. Furthermore, the results found point partially to the rejection of the research's alternative hypothesis, since intangible assets are positively related to stock returns when used as a parameter for the formation of portfolios in the CAPM model, measuring the return using the beta coefficient. Nevertheless, when added as an explanatory variable in the models, intangible assets are not significant in explaining the stock return, measured by the VAICTM. In the portfolios where the intangible assets were significant, they showed a negative relationship with the return on the shares listed on B3, indicating that this factor does not have a risk premium in the Brazilian market. As the VAICTM variable, in most of the portfolios, proved to be non-significant, one cannot state that the intangible assets, measured by VAICTM, are a factor to explain the stock return in the Brazilian stock market. This was confirmed by the second step regressions, in which the coefficients of the VAICTM model, obtained in the time series regressions, were not significant to explain the cross-section return of the portfolios of the ex-post sample. Therefore, given the results found, it is recommended to market agents, such as analysts and investors, the use of the CAPM model for decision making in the Brazilian stock market, since its simplicity, besides reducing the costs of portfolio maintenance, is more efficient than more complex models, since there is no clear and secure evidence of improved performance in factorial models applied to the Brazilian market